Electroencephalographic assessment of oral meloxicam, topical anaesthetic cream and cautery iron for mitigating acute pain in pigs (Sus scrofa) undergoing tail docking. (September 2017) - Kells, Nikki J.; Beausoleil, N.J.; Sutherland, M.A.; Morrison, R.M.; Johnson, Craig B.
Abstract: Objective: To evaluate the efficacy of oral meloxicam, topical anaesthetic cream and cautery iron in mitigating acute nociceptive responses of pigs to tail docking. Study design: A prospective, randomized, controlled experimental study. Animals: A total of 40 healthy Large White x Landrace pigs aged 21 ± 1 days, weighing 6.1 ± 0.9 kg. Methods: Pigs were randomly assigned to one of four treatments ( n = 10 per treatment): CONTROL: docked using clippers without analgesia; MEL: docked using clippers after administration of oral meloxicam; EMLA: docked using clippers after application of topical anaesthetic cream; and CAUT: docked using a cautery iron without analgesia. Anaesthesia was induced and maintained with halothane in oxygen. Following induction, end-tidal halothane was stabilized at 0.95–1.05% and electroencephalograph (EEG) recording commenced. After 5 minutes of baseline data collection, tail docking was performed and recording continued for a further 10 minutes. The EEG summary variables median frequency (F50), 95% spectral edge frequency (F95) and total power (PTOT ) were calculated for the baseline period and for consecutive 30-second intervals following docking. Results: Following docking, F50 increased and PTOT decreased significantly in CONTROL and MEL pigs. EMLA pigs exhibited no change in any variable, whilst CAUT pigs exhibited a reduction in PTOT but no change in F50. F50 was higher in control pigs than in EMLA pigs 30–60 seconds after docking ( p ≤ 0.01). PTOT was lower in CONTROL than in EMLA pigs 30–90 seconds after docking ( p < 0.03) and in CAUT pigs 60 seconds after docking ( p = 0.01). Conclusions and clinical relevance: Prior application of EMLA cream abolished EEG indicators of nociception in pigs docked using clippers. Docking using a cautery iron without analgesia ameliorated EEG indicators of nociception, relative to using clippers without analgesia. Prior administration of EMLA cream or the use of cautery instead of clippers may reduce the acute pain experienced by pigs undergoing tail docking.